FACTORS RELATED OF SMOKING BEHAVIOR MALE STUDENTS GRADE TWELVE IN SENIOR HIGH SCHOOL “Y” SEMARANG - Raumanen Afiana Lomboan; Bagoes Widjanarko; Sri Winarni (Jurnal Kesehatan Masyarakat (Undip), 2015)
Based on Global Adult Tobacco Survey, Indonesia is country with the highest smoker’s active, 67% man, 2,7% woman. The data showed that 5,4% of the ages 10-14 years children in Semarang City initiated to smoke daily. The main purpose of this research is to analyzee factors related to boy’s smoking at senior high school grade XII students in SMAN “Y” Semarang City. The mothod used in this research is quantitative method with case control study approach. Total of the populations are 166 and total of the samples are 76 by random sampling with 38 case sample, 38 control sample. There were 86,8% respondents ages is 17th. The analysis data uses univariate and bivariate with Chi-square statistical test (0.05 significance level). Most of respondents bad attitude (78,9%), simple achievable to cigarrette (59,2%), low exposure of cigarrette advertisements (50,0%), parenting of parents majority are democration (75%). The result of Chi-square test showed that there are no relationships between age respondents (p = 0,556 OR= 2,05), knowledge (p=0,169 OR=0,529), education of parents (p=0,287 OR= 0,457), smokers in families (p=0,063 OR=2,40), parenting of parents (p=0,185 OR=2,04), and income every months (p=0,818 OR=1,11). While attitude (p=0,000 OR=31,87), money for respondents everyday (p=0,022 OR=2,93), exposure of advertisements (p=0,000 OR=8,5), accesbility of cigarette (p=0,002 OR=4,43),  had p-value ≤ α (0,05), so it is concluded that there are relationships beetween those variables to smoking adolescence boy’s.